Structured clinical adjudication of Streptomyces spp. recovered from bronchoalveolar lavage in severe COVID-19 ARDS complicated by polymicrobial lower respiratory tract infection during invasive mechanical ventilation: a case report - Killen H. Briones-Claudett; Jaime Benites Solís; María Fernanda Pico Mendoza; Pedro Barberan-Torres; Diana C. Briones Márquez; Catherine Parreno; Ivonne Asqui; Anahí D. Briones-Zamora; Killen H. Briones-Zamora (Frontiers in Medicine, 2026)
Background Lower respiratory tract infections developing during invasive mechanical ventilation in patients with severe COVID-19 acute respiratory distress syndrome (ARDS) present important diagnostic and therapeutic challenges. Streptomyces spp., an uncommon respiratory isolate, frequently raises uncertainty regarding contamination, colonization, or clinically relevant infection because standardized criteria for clinical interpretation are lacking. Case presentation A 65-year-old woman with hypertension and obesity was admitted with severe COVID-19 ARDS requiring invasive mechanical ventilation after failure of high-flow nasal cannula. Baseline laboratory evaluation demonstrated leukocytosis (15.65 × 10 3 /μL), neutrophilia (14.73 × 10 3 /μL), lymphopenia (0.92 × 10 3 /μL; neutrophil-to-lymphocyte ratio 16), C-reactive protein 134 mg/L, ferritin 2,130 ng/mL, and procalcitonin 0.5 ng/mL. Bronchoscopy performed approximately 24–36 h after intubation revealed purulent secretions, and quantitative bronchoalveolar lavage culture recovered methicillin-resistant Staphylococcus aureus , CTX-M–positive Klebsiella pneumoniae , and Streptomyces spp. The BioFire FilmArray ® Pneumonia Panel confirmed MRSA and K. pneumoniae with CTX-M detection but does not include Streptomyces spp. A structured clinical adjudication process integrating specimen quality, microbiological findings, quantitative culture, host characteristics, radiological assessment, therapeutic context, and clinical evolution supported interpretation of Streptomyces spp. as most compatible with colonization rather than invasive pulmonary infection. Antimicrobial therapy was optimized with meropenem and linezolid according to the confirmed bacterial pathogens, without additional organism-specific therapy directed against Streptomyces . Conclusion This case illustrates the application of a structured clinical adjudication process to interpret recovery of an uncommon respiratory microorganism under conditions of microbiological uncertainty. Integration of quantitative bronchoalveolar lavage culture, rapid multiplex PCR, host factors, radiological assessment, and clinical evolution may support antimicrobial optimization while avoiding overinterpretation of uncommon respiratory isolates. The proposed approach should be regarded as an educational and descriptive clinical illustration requiring evaluation in future studies.